Electronic Land Certificate Ownership as an Effort to Protect the Personal Data Law of the Community - Ariansyah, Ruli; Barthos, Megawati; Sara, Rineke (Riviera Publishing, 2024)
Electronic land administration will replace systems that are still conventionally based. The aim of this research is to provide protection for personal data for people who have electronic land certificates so that they are right on target. Normative legal research uses qualitative methods with secondary data originating from documents, publications and research reports, and tertiary data functions as a guide and explanation for primary and secondary data. The results of the research conclude that ownership of electronic land certificates is necessary to improve the security of electronic systems owned by the government. UURI no. 5 of 1960 concerning Agrarian Principles and Regulation of the Minister of Agrarian Spatial Planning/National Land Agency No. 1 of 2021 concerning Electronic Certificates which provides new technology in land registration services. Staff to support administration to use information technology and data validation. As a result, speed and innovation are needed to secure multiple uses of personal data. Therefore, electronic or digital certificates must be socialized first to the public to better understand and provide legal certainty in their application